How fertility preservation guidelines have progressed worldwide: Potential implications and inspiration. Issue 1 (March 2022) - Chen, Min-Xin; Zhang, Ying; Cai, Qing-Qing; Zhang, Shuo; Xu, Ran; Chen, Hua; Kang, Yu; Wu, Yue; Chian, Ri-Cheng; Xu, Cong-Jian
Abstract : Abstract: To summarize fertility preservation (FP) guidelines and consensus provided by medical facilities worldwide. Five reference databases (PubMed/Embase, China BioMedical Literature Database, ClinicalKey, Wanfang Data, and China Knowledge Resource Integrated) and 7 guideline databases (Guideline International Network, National Collaborating Centre for Women's and Children's Health, National Guideline Clearinghouse, The National Institute for Health and Care Excellence, Scottish Intercollegiate Guidelines Network, New Zealand Guideline Group, and Canadian Medical Association infobase) were searched. Official websites of societies were searched to find relevant guidelines and consensus, and guidelines and published systematic reviews and consensus were reviewed from inception through May 2021. A literature search was performed regarding guidance offered in professional facilities, and 304 records (including 4 in Chinese) of existing guidelines for full-text review were found. Moreover, 55 guidelines were identified after a manual search. The literature review demonstrated that FP guidance and options were unevenly distributed worldwide for women who wanted to post-pone pregnancy or had impaired fertility after gonadal toxicity. With promising cancer survival rates and diversified family decisions, more attention should be paid to the improvement and update of accessible guidelines and regulatory infrastructure to inform patients about the available options and empower them to make informed choices. Restrictions to such services can be gradually eased due to the efficacy and safety of certain FP techniques for the right candidates to initiate pregnancy conception.